2017
DOI: 10.1038/s41598-017-16774-8
|View full text |Cite
|
Sign up to set email alerts
|

Monkeys share the neurophysiological basis for encoding sound periodicities captured by the frequency-following response with humans

Abstract: The extraction and encoding of acoustical temporal regularities are fundamental for human cognitive auditory abilities such as speech or beat entrainment. Because the comparison of the neural sensitivity to temporal regularities between human and animals is fundamental to relate non-invasive measures of auditory processing to their neuronal basis, here we compared the neural representation of auditory periodicities between human and non-human primates by measuring scalp-recorded frequency-following response (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 79 publications
3
24
0
1
Order By: Relevance
“…In addition, the comparison of beat‐entrainment abilities between human and nonhuman primates can be complemented with noninvasive electrophysiological experiments that allow the investigation of the neural correlates of beat perception, a precondition for rhythmic entrainment . Indeed, we have studied the encoding of auditory periodicity through scalp‐recorded evoked potentials while awake monkeys passively listened to periodic auditory stimuli with different levels of metrical hierarchy . We demonstrated that macaques share with humans the neurophysiological mechanisms to represent fast acoustic periodicities by exhibiting a human‐homologous frequency‐following response (FFR) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the comparison of beat‐entrainment abilities between human and nonhuman primates can be complemented with noninvasive electrophysiological experiments that allow the investigation of the neural correlates of beat perception, a precondition for rhythmic entrainment . Indeed, we have studied the encoding of auditory periodicity through scalp‐recorded evoked potentials while awake monkeys passively listened to periodic auditory stimuli with different levels of metrical hierarchy . We demonstrated that macaques share with humans the neurophysiological mechanisms to represent fast acoustic periodicities by exhibiting a human‐homologous frequency‐following response (FFR) .…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50] Indeed, we have studied the encoding of auditory periodicity through scalp-recorded evoked potentials while awake monkeys passively listened to periodic auditory stimuli with different levels of metrical hierarchy. 28,51 We demonstrated that macaques share with humans the neurophysiological mechanisms to represent fast acoustic periodicities 51 by exhibiting a humanhomologous frequency-following response (FFR). 49 Important for the present discussion is the fact that human participants that can entrain with high precision to an external beat also show larger intertrial consistency of the FFR potential, [52][53][54] suggesting a partial overlap between auditory circuits underlying the FFR and neural circuits involved in beat entrainment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, zebra finches produce temporally structured syllable sequences and can perceptually group auditory input . Rhesus monkeys can produce single intervals and synchronize to a metronome, while macaques display auditory grouping . So far, though there is no evidence that any one of these species can form hierarchical temporal structure as found in human speech and music.…”
Section: Time and Rhythm: Linking Neural Systems And Behaviormentioning
confidence: 99%
“…16 Rhesus monkeys can produce single intervals and synchronize to a metronome, 180 while macaques display auditory grouping. 181,182 So far, though there is no evidence that any one of these species can form hierarchical temporal structure as found in human speech and music. One explanation, while still speculative, could be that the strict serial order of events in time does not yet define rule-based behavior beyond local dependencies.…”
Section: Time and Rhythm: Linking Neural Systems And Behaviormentioning
confidence: 99%
“…FFRs have been used to study the auditory system's ability to process temporal periodicities [59][60][61][62][63] and it is known that FFRs can occur in response to missing fundamental frequencies 64 .…”
Section: Listening To Fast Periodic Vocalizations Boosts the Bats' Hementioning
confidence: 99%